MANAGING THE INTELLIGENT TOOLS IN THE STUDY OF SOIL BIODIVERSITY ACTIVITY AS AN ECOSYSTEM SERVICE PROVIDER - Daniela RĂDUCU; Anca-Rovena LĂCĂTUȘU; Horia DOMNARIU; Alina EFTENE; Alexandrina MANEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The use of local leaders and leader farmers in extension programs has been common in most countries. Through the analysis of a case study, this paper aims to evaluate the effectiveness of leader horticultural producers in increasing the quantitative and qualitative efficiency of horticultural products in Iran from the gardeners' perspective . The statistical population of the study was composed of horticultural producers in Kerman province in 2015-2016 (=310). Sixty gardeners were picked up by Cochran formula and random cluster sampling. The research instrument was a questionnaire and the research used a descriptive-correlational design. More than half of the gardeners had no knowledge about the leader producers in their area, and had never visited any sample farm. The leader producers were the fifth source of information, with only 11.1% of gardeners had received information from them. Overall, more than 60 percent of gardeners cited the effectiveness of leader producers as average. Gardeners who had less experience, higher education, more area under cultivation, and a high number of visits to agricultural departments, and were more satisfied with agricultural profession found leader producers to be more effective. The findings confirm the weak position of the leader producers among gardeners.